Pengelolaan Tanaman Penutup Tanah untuk Meningkatkan Produksi Jagung Manis Di Lahan Kering Vertisol Lombok - Herman Suheri; Komang Damar Jaya; Bambang Hari Kusumo (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
One of the obstacles in increasing maize production in Indonesia is the low efficiency of fertilizer use by plants as a result of low levels of organic matter in the soil. Although it only occupies a portion of approximately 2-10%, the role played by organic matter in the soil is very large, both in physical, chemical and biological aspects. One of the practical and efficient alternatives to increase organic matter in the soil is through the management of cover crops (TPT). In this study, individually or after being combined into one, three types of TPT were stocked before the harvest of the predecessor plant (rice). As a comparison, plots without TPT were also provided. Rice litter together with TPT biomass from each TPT treatment was returned to the soil after rice was harvested in a separate plot pattern. In each TPT treatment plot, fertilization treatments were made with a dose of 0 kg/ha NPK, 100 kg/ha NPK, 200 kg/ha NPK and 300 kg/ha NPK. The experimental results showed that TPT biomass had a positive impact on increasing the growth and yield of sweet corn on vertisol soils. Provision of cover crops in the form of a mixture of cowpea, mung bean and krotalaria tended to have a better effect than individual administration. From the results of this experiment, it is also known that the provision of precursor plant biomass combined with TPT biomass can reduce the use of chemical fertilizers by 50-60% of the maximum plant requirement.